Digital Applications and the Transformation of Financial Record-Keeping Among Generation Z - Sutrisno, Hadi; Yasmin, Syari’ah Malika (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
Despite the widespread adoption of digital financial tools, the transition from manual to automated financial record-keeping among digital natives remains underexplored. This study aims to examine the role of digital applications in transforming personal financial management practices among Generation Z in Indonesia. A descriptive qualitative approach was employed using semi-structured interviews conducted between August and October 2025 with students and young entrepreneurs at STIE Ganesha, selected through purposive sampling. The findings indicate that digital financial applications significantly shift financial practices from informal and inconsistent methods toward more structured and data-driven approaches. Commonly used applications, such as Money Lover, Money+, and Walletya, support expense tracking and financial evaluation. However, the level of utilization varies depending on users’ self-control and digital financial literacy. While these tools enhance financial awareness, they do not necessarily lead to sustained financial discipline. This study highlights that digital applications function primarily as facilitators rather than determinants of financial behavior. Their effectiveness depends on users’ ability to interpret and apply financial information. Therefore, strengthening digital financial literacy is essential to ensure that technology adoption leads to more sustainable financial practices among Generation Z